A CLUSTER MODEL FOR HYBRIDS - Antunes, ACB; Decastro, A. S. (Editrice Compositori Bologna, 1994)
A model for describing hybrid spectroscopy similar to the diquark model for baryons is presented. Mass and r.m.s. radii are calculated and compared with experimental results.